2007
DOI: 10.1055/s-2006-927238
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound and Mammography Guided Wire Marking of Non-Palpable Breast Lesions: Analysis of 741 Cases

Abstract: Sonography directed wire localisation appears to be superior to the respective mammographic method. Ultrasound guided wire marking should be considered the preferred method for all mammographic lesions with an ultrasonographic equivalent and no micro-calcifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
0
10
0
5
Order By: Relevance
“…Previous research demonstrates that detection rate of breast microcalcifications using ultrasound alone is low, and it is only 30-50% of detection rate of mammography X-ray (42,43). It was reported that the combination of ultrasound and X ray mammography was useful to detect the non-palpable lesions and identify the breast lesions (benign or malignant) (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research demonstrates that detection rate of breast microcalcifications using ultrasound alone is low, and it is only 30-50% of detection rate of mammography X-ray (42,43). It was reported that the combination of ultrasound and X ray mammography was useful to detect the non-palpable lesions and identify the breast lesions (benign or malignant) (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…With improving histological and cytological techniques, particularly in immunohistochemical analysis, histological and possibly molecular examination may determine with more certainty the probable underlying primary tumour site and can predict sensitivity to chemotheraputic drugs in some cases [5]. In cases where surgical biopsy remains the preferred diagnostic approach, pre-operative tumour localisation can be performed with image guidance in many situations; an example of this is wire-localisation prior to excisional breast biopsy [6] and in the chest to guide video-assisted thorascopic surgery (VATS) for removal of lung nodules that would otherwise require open thoracotomy [7]. Increasingly, percutaneous biopsy is utilised for microbiological diagnosis of lesions suspicious for opportunistic infections (particularly fungal) in oncology patients with febrile neutropenia [8].…”
Section: Interventional Radiology In the Diagnosis Of Cancermentioning
confidence: 99%
“…Vonhohem diagnostischem Wert ist der US aber bei Frauen mit einem dichten DrüsengewebeA CR Grad 3u nd 4a uch in der Früherkennung, wo die Sensitivitätinder Erfassung vonmalignen Läsionen durch US im Vergleich zur Mammografie alleine erhöht wird [3,6]. Darüber hinaus lassen sich mit dem US auch bildgesteuerte Biopsien oder präoperativeDrahtmarkierungen durchführen [7]. Immer wieder genannte Nachteile des Mamma-US sind vorallem der relativ hohe zeitliche Aufwand fürd en Untersucher sowie eine Abhängigkeit der Qualitätd er Methode vond er persönlichen Erfahrung des Untersuchers.…”
Section: Abstract !unclassified
“…Die Untersuchungsdauer der Ultraschalluntersuchungenw urde vond er dienstführenden RT-Mitarbeiterin mithilfee iner Stoppuhr gemessen, wobei Untersuchungszeiten (Dauer der eigentlichen Untersuchung)u nd Rüstzeiten (Vor-u nd Nachbetreuung der Patientinnen inklusiveLagerung)erhoben wurden. Die ABUS-Bilddatensätzew urden unabhängigv oneinander von einer im Mamma-Ultraschall erfahrene Radiologin (15 Jahre Erfahrung im Mamma-US, Befunder 1) und einem Radiologen mit geringer Erfahrung (10 MonateE rfahrung mit Mamma-US) (Befunder 2) nach BI-RADS-Kriterien befundet[7]. DieB efundung der ABUS-Bilddatensätzee rfolgtei nK enntnis der Zuweisungsdiagnose und des schriftlich festgehaltenen Tastbefunds, der Inspektion und der Eigen-und Familienanamnese.D ie Befunder hatten jedoch keinen Einblick in die Bilddaten oder den Befund des handgeführten Ultraschalls.…”
unclassified